Dual trocar laparoscopy improves reduced-port surgery of the distal pancreas. Issue 5 (1st June 2022) - Mittermair, Christof; Weiss, Michael; Schirnhofer, Jan; Brunner, Eberhard; Obrist, Christian; Biebl, Matthias; Hell, Tobias; Weiss, Helmut
Abstract: Background: The technical feasibility of transumbilical single-incision surgery (SIL) for pancreatic resections has been demonstrated. However, this technique is hampered by the limited degrees of freedom for instrument handling. Dual-incision laparoscopy (DIL) with an additional trocar may simplify dissection and allow drainage. Material and methods: Between December 2009 and May 2017, 21 patients were treated with SIL (12/2009 to 01/2014) or DIL (02/2014 to 05/2017) pancreatic resection. All data were collected in a database and retrospectively analysed. Results: Demographic parameters of the patients did not differ significantly in the DIL or the SIL group. No conversion to open surgery was required. No intraoperative complication occurred in either group. The surgical difficulty score was significantly higher in the SIL group (4.4 ± 1.56 vs 2.18 ± 1.95; p = .006). Postoperative serum amylase levels were higher (101.9 U/l ± 50.11 vs 48.91 U/l ± 35.20; p = .01) and return to normal levels (6.4 ± 9.66 days vs 2.09 ± 1.98 days; p = .045) was later in the SIL group. Three complications requiring radiological or surgical intervention were witnessed in the SIL group and one complication in the DIL group ( p = .42). Conclusion: DIL surgery is a safe and feasible alternative to SIL surgery, facilitating key steps of distal pancreatic tail resection.